Cantiones sacrae II (1591) - Byrd, William 1539/40-1623; Brown, Alan 1941-; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1981)
The Liber Secundus Sacrarum Cantionum appeared in November 1591, and was printed, like its predecessor, by Thomas East. Biblical and liturgical sources provided texts for its 21 motets, most of them sombre in tone. The noted scholar Joseph Kerman has observed that in these pieces, Byrd may have been voicing ‘prayers, exhortations and protests on behalf of the English Roman Catholic community’.
Keywords: 16th Century (1501-1600); Motet